Discursivizações sobre Ayrton Senna e certa representação de brasilidade - Leite, João de Deus (2010)
The goal of this work is to analyze certain sayings produced media about Ayrton Senna Formula 1 Brazilian driver, who won three titles of Formula One World: 1988 had Senna winning his first Formula One World Championship; 1990 once again had Senna becoming World Champion and in 1991, he became the World Driving Champion for the third and last time of his career. To do this we will take into account the analysis of discourse in French perspective driven by Michael Pêcheux. We are interested in two questions, namely, the first of which is that Senna was represented as certain discourses of media, such as the Brazilian model, as the pilot who could not be defeated, as the genuine Brazilian hero, the second question has to do with the fact we find that the considerations about Senna were based on a categorical approach to attribute and feature as if they were enough of one for establishing a unit with regard to the Brazilian nation. It is media saying, which are tightly bound in a mode of writing, which is different from the canonical writing one that seeks to build an effect of accuracy of the facts and a prevalence of the Imaginary. In this case study we will embody the following research question: Given the way of structuring one for journalistic texts as the subjective representation of Ayrton Senna is produced? Based on the texts which we take as support we assume the hypothesis that the journalistic activity related to Ayrton Senna promotes a homogenizing effect on the subjective representation of Senna, sharpening, a certain ideal of national ego, which is constructed through the image of invincible pilot. Thus, from discursive sequences, we intend to show that some associations of adjectives and of adverbs, and also certain culturally block constituted imaginative glimpses a metaphorical construction of Ayrton as a pilot invincible. Such construction points to a picture of him as a model: model of pilot towards model of Brazilian man. Finally it is worth noting that the reflection made by Bhabha (1990) about the prospect of nation as narration is very relevant to this study, since for him the national text is marked by the articulation of certain principles and certain narrative difference imposed by the positions narratives nations.